Local reality and the climate change adaptation dilemma : beyond technical fixes and 'business as usual' : dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Resource and Environmental Planning at Massey University, Manawatu, New Zealand - Schneider, Paul Philipp (Massey University, 2014)
Climatic changes are being recorded and experienced and coastal communities are already adversely affected with impacts projected to intensify many times over in coming decades. Adaptation is embryonic at best and needs to take place in the face of already diverse and contested interests presenting coastal communities with a dilemma: Well-‐intentioned approaches dressed in the rhetoric of adaptation (as legislative and guidance imperatives, and case law) are compounding existing problems by fostering unsustainable and maladaptative development. While ‘business as usual’ dominates, the need for an overcoming of conventional approaches through new governance modalities has never been more urgent and will become increasingly compelling in the future. This thesis focuses on New Zealand’s Coromandel Peninsula in an ethnographic case study that underscores the need to understand the messy local factors and power networks encasing climate change adaptation barriers and opportunities. Drawing upon and combining insights from political ecology and environmental planning, and building on a framework to diagnose barriers to climate change adaptation, this research discloses an urgent need for adaptation to dismantle currently gridlocked structures and evolve from persistent technical solutions, particularly against the background of coastal erosion. The findings show that adaptation must first and foremost be addressed at the community level and be integral to creative (environmental) governance approaches. The navigational chart for overcoming barriers requires a new view of the complexities involved as part of the adaptation processes.
Keywords: Climate change; Coastal changes; Coastal communities; Coromandel peninsula; Climate change adaptation; Coastal erosion